Enhancing In Vivo Electroporation Efficiency through Hyaluronidase: Insights into Plasmid Distribution and Optimization Strategies - Debnath Maji; Verónica Miguela; Andrew D. Cameron; Delcora A. Campbell; Linda Sasset; Xin Yao; Andy T. Thompson; Carleigh Sussman; David Yang; Robert Miller; Marek M. Drozdz; Rachel A. Liberatore (MDPI AG, 2024)
Electroporation (EP) stands out as a promising non-viral plasmid delivery strategy, although achieving optimal transfection efficiency in vivo remains a challenge. A noteworthy advancement in the field of in vivo EP is the application of hyaluronidase, an enzyme with the capacity to degrade hyaluronic acid in the extracellular matrix, which thereby enhances DNA transfer efficiency by 2- to 3-fold. This paper focuses on elucidating the mechanism of hyaluronidase's impact on transfection efficiency. We demonstrate that hyaluronidase promotes a more uniform distribution of plasmid DNA (pDNA) within skeletal muscle. Additionally, our study investigates the effect of the timing of hyaluronidase pretreatment on EP efficiency by including time intervals of 0, 5, and 30 min between hyaluronidase treatment and the application of pulses. Serum levels of the pDNA-encoded transgene reveal a minimal influence of the hyaluronidase pretreatment time on the final serum protein levels following delivery in both mice and rabbit models. Leveraging bioimpedance measurements, we capture morphological changes in muscle induced by hyaluronidase treatment, which result in a varied pDNA distribution. Subsequently, these findings are employed to optimize EP electrical parameters following hyaluronidase treatment in animal models. This paper offers novel insights into the potential of hyaluronidase in enhancing the effectiveness of in vivo EP, as well as guides optimized electroporation strategies following hyaluronidase use.